Infection Biomarkers Based on Metabolomics - Araújo, Rúben (2022)
Funding Information: Funding: This work was supported by the project grant DSAIPA/DS/0117/2020 supported by Fundação para a Ciência e a Tecnologia, Portugal; and by the project grant NeproMD/ISEL/2020 financed by Instituto Politécnico de Lisboa.